Do pirates play fair? Testing copyright awareness of sports viewers. Issue 6 (3rd June 2017) - Krawczyk, Michał; Tyrowicz, Joanna; Kukla-Gryz, Anna; Hardy, Wojciech
ABSTRACT: Ethical norms are believed to be followed more loosely on the Internet than in the 'real world'. This proposition is often evoked to explain the prevalence of so-called digital piracy. In this study, we provide evidence from a vignette experiment that contradicts this claim. Analysing the case of sports broadcast, we compare explicitly the ethical judgement of legal and illegal sharing in the offline and online contexts. We find that the norms concerning legality, availability of alternatives and deriving material benefits from sharing content do not differ substantially between the virtual and real worlds. We also test explicitly for the role of legal awareness and find that emphasising what is prohibited (copyright infringement) is less effective than focusing on what is permitted (fair use) in reducing the disparity between legal and ethical norms.